Controlling Thermal Expansion Behaviors of Fence-Like Metal-Organic Frameworks by Varying/Mixing Metal Ions - Zhou, Hao-Long; Zhang, Jie-Peng; Chen, Xiao-Ming (Frontiers in Chemistry, 2018)
Solvothermal reactions of 3-(4-pyridyl)-benzoic acid (Hpba) with a series of transition metal ions yielded isostructral metal-organic frameworks [M(pba)2]•2DMA (MCF-52; M = Ni2+, Co2+, Zn2+, Cd2+, or mixed Zn2+/Cd2+; DMA = N,N-dimethylacetamide) possessing two-dimensional fence-like coordination networks based on mononuclear 4-connected metal nodes and 2-connected organic ligands. Variable-temperature single-crystal X-ray diffraction studies of these materials revealed huge positive and negative thermal expansions with || > 150×10-6 K-1, in which the larger metal ions give the larger thermal expansion coefficients, because the increased space not only enhance the ligand vibrational motion and hinged-fence effect, but also allow larger changes of steric hindrance between the layers. In addition, the solid-solution crystal with mixed metal ions further validates the abundant thermal expansion mechanisms of these metal-organic layers.